Ultralong UV/mechano-excited room temperature phosphorescence from purely organic cluster excitons - Xuepeng Zhang (Nature Portfolio, 2019)
Purely organic ultralong room temperature phosphorescence (URTP) attracts attention but high efficiencies are rarely achieved. Here the authors use ultrafast spectroscopy to investigate a system of 1,8-naphthalic anhydride in organic hosts and reveal that a cluster exciton forms as a transient state before the guest acts as an energy trap for the URTP state.